CLINICAL AND ECONOMICAL RATIONALES OF CARDIOVASCULAR RISK EVALUATION AT WORKPLACE - A. V. Kontsevaya; A. M. Kalinina; Yu. M. Pozdnyakov; S. V. Belonosova; M. B. Khudyakov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study clinical and economical rationales for cardiovascular risk evaluation at workplace (on example of the personnel of engineering research institute).Material and methods. Complex preventive screening with evaluation of arterial hypertension (HT) prevalence, cardiovascular risk level and requirement for risk factors correction is performed. Economical rationales for preventive screening (with estimation of the total costs, costs for one studied person and costs for revealing of one person needed in preventive actions) are also estimated.Results. Preventive screening in the organized collective found new HT cases (12,2%), high and very high cardiovascular risk (58,6%). The desire for risk factors correction is found in 13,0-59,0% of workers. The total costs for preventive screening of 468 persons were 174413 rubles in 3,5 months. Costs for examination of one worker were 561,7 rubles. Costs for detecting of one worker requiring preventive actions were from 635,6 to 3077,4 rublesConclusion. There are rationales for preventive screening of cardiovascular risk and desire to correct it at the workplace.